2014
DOI: 10.1111/tri.12300
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic risk factors and long-term graft function after paediatric renal transplantation

Abstract: SummaryThe aim of this study was to evaluate metabolic risk factors and their impact on long-term allograft function in paediatric renal transplant (RTx) patients. We reviewed the medical records of 210 RTx patients who underwent transplantation at a median age of 4.5 years (range 0.7-18.2) and a median follow-up of 7.0 years (range 1.5-18.0). Data on lipid and glucose metabolism, uric acid levels, weight and blood pressure were collected up to 13 years post-RTx, and the findings were correlated with the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Many studies have linked hyperuricaemia with a worse kidney allograft outcome, and indicated a possible benefit from treating asymptomatic hyperuricaemia . Episodes of acute cellular rejection and chronic antibody‐mediated rejection decrease graft survival .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have linked hyperuricaemia with a worse kidney allograft outcome, and indicated a possible benefit from treating asymptomatic hyperuricaemia . Episodes of acute cellular rejection and chronic antibody‐mediated rejection decrease graft survival .…”
Section: Discussionmentioning
confidence: 99%
“…The data on metabolic risk factors among pediatric RTx patients are still limited. In a cohort of patients mostly transplanted before the age of 2 years, metabolic syndrome, overweight, hypertension, and type 2 diabetes were observed in 14-19 %, 20-23 %, 61-87 %, and 3-5 % of patients at 1.5-5 years after RTx, respectively [45]. Higher incidences of these risk factors, however, have been reported in pediatric RTx patients [80][81][82][83].…”
Section: Metabolic Risk Factorsmentioning
confidence: 99%
“…1 In infants, the kidney graft can be placed intraperitoneally (a) or extraperitoneally (b) [44]. The other possibility is to switch to low-dose (0.1 mg/kg/ day), every-other-day medication, which also effectively abolishes the steroid side effects [45,46].…”
Section: Peri-and Postoperative Managementmentioning
confidence: 99%
“…The prevalence of CKD was 25% up to six months after CLKT in small study . We have previously shown that GFR remains relatively stable from one up to five years after adult and pediatric LT and also after pediatric KT . Others have reported that GFR remains steady or slightly worsens up to five years after adult and pediatric CLKT .…”
Section: Introductionmentioning
confidence: 83%